1994
DOI: 10.1017/s0140525x00034026
|View full text |Cite
|
Sign up to set email alerts
|

The representing brain: Neural correlates of motor intention and imagery

Abstract: This paper concerns how motor actions are neurally represented and coded. Action planning and motor preparation can be studied using a specific type of representational activity, motor imagery. A close functional equivalence between motor imagery and motor preparation is suggested by the positive effects of imagining movements on motor learning, the similarity between the neural structures involved, and the similar physiological correlates observed in both imaging and preparing. The content of motor representa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

70
1,327
4
56

Year Published

1998
1998
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 2,127 publications
(1,457 citation statements)
references
References 231 publications
70
1,327
4
56
Order By: Relevance
“…More recently, Vogt (1995) found that the temporal consistency in producing sequential arm movements improved to the same extent through mental, observational, and physical practice. Whereas the equivalence of motor imagery and physical practice could be expected from earlier behavioral and neurophysiological work (see Jeannerod, 1994Jeannerod, , 1997Jeannerod & Decety, 1995), the equivalence of observational and physical practice was unexpected. It indicates that motor structures are already involved during movement observation and thus provides a theoretical alternative to distinct stage models.…”
Section: From Perception To Actionmentioning
confidence: 74%
See 2 more Smart Citations
“…More recently, Vogt (1995) found that the temporal consistency in producing sequential arm movements improved to the same extent through mental, observational, and physical practice. Whereas the equivalence of motor imagery and physical practice could be expected from earlier behavioral and neurophysiological work (see Jeannerod, 1994Jeannerod, , 1997Jeannerod & Decety, 1995), the equivalence of observational and physical practice was unexpected. It indicates that motor structures are already involved during movement observation and thus provides a theoretical alternative to distinct stage models.…”
Section: From Perception To Actionmentioning
confidence: 74%
“…In both of these cases of intermodal matching, however, sensory inputs from two modalities were present at some point, whereas in our visual test, participants would have had to generate expected kinesthetic signals from the visual input. Such visually induced kinesthetic images are certainly conceivable (Jeannerod, 1994(Jeannerod, , 1997. Our main discomfort with this explanation for APT is, however, that we would be left with a number of arguments for the involvement of visuomotor couplings in the visual task (see Introduction and Discussion of Experiment 1), but these couplings would not serve any function.…”
Section: Cross-modal Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…It is assumed that motor imagery is an internal simulation of the overt movement program (Jeannerod, 1994;Jeannerod and Frak, 1999). Thus, the essential process to perform motor imagery is the programming and planning of the movement in premotor cortices.…”
Section: Comparison Of Movement Modesmentioning
confidence: 99%
“…the mental simulation of a motor act. It has been suggested that kinesthetic motor imagery involves the same neural network as motor planning (Jeannerod, 1994;Jeannerod and Frak, 1999), which in turn is thought to rely on the same motor structures as motor execution (Johnson-Frey, 2004;Munzert et al, 2009;Sharma et al, 2006). In support of this view, motor imagery shares a number of similarities with overt movement execution, such as behavioral (Decety and Jeannerod, 1995) and physiological parameters (Kranczioch et al, 2008(Kranczioch et al, , 2009, and, importantly, the functional neuroanatomical correlates (Decety, 1996;Lotze and Halsband, 2006;Porro et al, 1996;Szameitat et al, 2007aSzameitat et al, , 2007b.…”
Section: Introductionmentioning
confidence: 98%